2014
DOI: 10.1007/s12033-014-9775-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Strategies for the Production of FMDV Empty Capsids Using the Baculovirus Vector System

Abstract: Recombinant FMDV empty capsids have been produced in insect cells and larvae using the baculovirus expression system, although protein yield and efficiency of capsid assembly have been highly variable. In this work, two strategies were compared for the expression of FMDV A/Arg/01 empty capsids: infection with a dual-promoter baculovirus vector coding for the capsid precursor (P12A) and the protease 3C under the control of the polyhedrin and p10 promoters, respectively (BacP12A-3C), or a single-promoter vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…VLPs developed for an Indian vaccine strain protected guinea pigs against homologous challenge [83]. Several improvements have been made in the production of VLPs using the dual promoter vector, 3Cpro [84], or using a bicistronic complementary DNA cassette containing two open reading frames encoding an FMDV capsid gene (P1-2A) and 3Cpro separated by an internal ribosome entry site [85]. In another study, the mutation in the VP2 region increased the thermostability of VLPs and produced sufficient protection in guinea pigs [86].…”
Section: Trends and Advances In Vaccines Against Fmdvmentioning
confidence: 99%
“…VLPs developed for an Indian vaccine strain protected guinea pigs against homologous challenge [83]. Several improvements have been made in the production of VLPs using the dual promoter vector, 3Cpro [84], or using a bicistronic complementary DNA cassette containing two open reading frames encoding an FMDV capsid gene (P1-2A) and 3Cpro separated by an internal ribosome entry site [85]. In another study, the mutation in the VP2 region increased the thermostability of VLPs and produced sufficient protection in guinea pigs [86].…”
Section: Trends and Advances In Vaccines Against Fmdvmentioning
confidence: 99%
“…Currently, FMD vaccine studies using an inactivated vaccine, modified virus inactivated vaccine (DIVA vaccine) [ 24 ], viral vector vaccine [ 25 ], adenovirus [ 26 , 27 , 28 ], virus-like particle (VLP) vaccine (bacterial) [ 29 ], baculovirus [ 30 , 31 ], plant-produced empty capsids [ 32 , 33 ], peptide vaccine (Poly(I:C)) [ 34 ], CpG [ 35 ], plant based recombinant vaccine (alfalfa [ 36 ], chloroplast of tobacco [ 37 ]), RNA vaccine [ 38 ], DNA vaccine (cDNA [ 39 , 40 ], electroporation [ 41 ], T cell [ 42 , 43 , 44 ], B cell [ 45 , 46 ] epitope, APC targeting [ 47 ]), live attenuated vaccine [ 48 , 49 , 50 , 51 ], and antiviral agent [ 52 , 53 ] are underway. However, no high-quality FMD vaccines that surpass the efficacy of the inactivated vaccine have been successfully developed to date.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently two forms of FMDV VLP vaccines: one composed of FMDV capsid proteins and one composed of chimeric FMDV VLPs created by incorporating critical epitopes from multiple serotypes. FMDV VLPs or chimeric VLPs can be efficiently expressed in E. coli, mammalian cells, and insect expression systems (Silva, et al 2013;Xiao, et al 2016;Oem, et al 2007;Felberbaum 2015;Ruiz, et al 2014;Gullberg, et al 2013). Previous research has shown that FMDV VLPs, as FMDV vaccines, can induce long-lasting humoral and cellular immune responses.…”
Section: Foot and Mouth Disease Virus (Fmdv)mentioning
confidence: 99%